Electrophysiological evidence of stroboscopic training in elite handball players: Visual evoked potentials study - Zwierko, T.; Jedziniak, W.; Domaradzki, J.; Zwierko, M.; Opolska, M.; Lubinski, W. (Journal of Human Kinetics, 2024)
Stroboscopic training enhances perceptual cognition and motor skills; however, neurophysiological mechanisms underlying this adaptation are not fully understood. This study aimed to investigate the effects of a six-week stroboscopic training program on the conductivity of the visual pathway in elite handball players, specifically related to their visual processing of retinal location and viewing conditions. The study included 22 handball players who were randomly assigned to an experimental or a control group. Both groups performed handball-specific in-situ tasks, but only the experimental group underwent stroboscopic training. Participants were assessed three times using visually evoked potential recordings measured by P100 implicit time and amplitude under three viewing conditions (dominant eye, non-dominant eye, and binocular) and two retinal locations (extra-foveal and foveal vision) before and after the six-week training period, and again four weeks later. The results showed a significant TIME vs. GROUP effect of P100 implicit time for the dominant eye in extra-foveal vision (F2,40 = 5.20, p = 0.010, np2 = 0.206), extra-foveal binocular viewing (F2,40 = 3.32, p = 0.046, np2 = 0.142), and dominant eye foveal vision (F2,40 = 4.07, p = 0.025, np2 = 0.169). Stroboscopic training significantly improved early visual processing by reducing the P100 implicit time for the dominant eye and binocular vision, particularly in extra-foveal vision. The improvements were more noticeable in the short compared to the long term.